Analytical characterization of historical mortars from the Roman villa of Frielas (Loures, Portugal) - Tanjil, Tanjil (2024)
The analytical characterization of mortar samples from the Roman archaeological site of Frielas, located in Lisbon, Portugal; was carried out by means of X-diffraction (XRD), thermogravimetry (TGA-DTG), optical microscopy and scanning electron microscopy coupled with energy-dispersive spectroscopy (SEM-EDS), acid attack and granulometric analysis. A total of eighteen mortar samples were collected from the different structures of the villa with different functional uses (render, filler, and floor). The results showed a similar composition of binder, while differences in aggregates allowed to establish several groups. Results were discussed as evidence of manufacturing techniques, production technologies, and provenance of possible raw materials. There was no prominent variation that can suggest a different chronology between the group of samples. Though, it is assumed that there might be some renovation, restoration, or partial rebuilding that occurred in the same period. In terms of production technology, proportions ruled by Vitruvius were not followed.